Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/acr.20675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐speed power training on muscle performance, function, and pain in older adults with knee osteoarthritis: A pilot investigation

Abstract: Objective. To examine the effect of high-speed power training (HSPT) on muscle performance, mobility-based function, and pain in older adults with knee osteoarthritis. Methods. Thirty-three participants (mean ؎ SD age 67.6 ؎ 6.8 years) were randomized to HSPT (n ‫؍‬ 12), slow-speed strength training (SSST; n ‫؍‬ 10), or control (CON; n ‫؍‬ 11) for a 12-week intervention. HSPT performed 3 sets of 12-14 repetitions at 40% of the 1-repetition maximum (1RM) "as fast as possible," SSST performed 3 sets of 8 -10 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
(34 reference statements)
1
51
0
3
Order By: Relevance
“…Most samples were composed of subjects of each gender 21,22,[24][25][26][27][28][29][30] with age above 50 years. [23][24][25][26][28][29][30][31] Eight studies had small samples, with less than 30 subjects per group.…”
Section: Resistance Exercises To Improve Pain And/or Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most samples were composed of subjects of each gender 21,22,[24][25][26][27][28][29][30] with age above 50 years. [23][24][25][26][28][29][30][31] Eight studies had small samples, with less than 30 subjects per group.…”
Section: Resistance Exercises To Improve Pain And/or Functionmentioning
confidence: 99%
“…[23][24][25][26][28][29][30][31] Eight studies had small samples, with less than 30 subjects per group. [19][20][21][22]27,[29][30][31] The studies analyzed the impact of exercises on the functional capacity, especially with the tests going up and down stairs, 22,23,29,30 getting up from a chair, 21,22,29,30,31 the WOMAC physical function subscale, 26,29,30,31 and walking. [19][20][21][22][24][25][26][27][28][29][30][31] Pain was evaluated in most studies with the WOMAC pain subscale.…”
Section: Resistance Exercises To Improve Pain And/or Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated that muscle power attributes to patients' functional ability and would play a role in proprioception. 19,20 Consequently Sayers et al 21 conducted a study that investigated the benefits of high-speed power training (HSPT) and slow speed strength training (SSST) when compared to a control group, which performed stretching and warm up exercises. The results demonstrated an improvement in function and pain across all three groups.…”
Section: Review Of Literaturementioning
confidence: 99%